2019
DOI: 10.1111/ijfs.14412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peeling and unpeeling on yield, chemical structure, morphology and pasting properties of starch extracted from three diverse potato cultivars of Pakistan

Abstract: The current study investigates the comparison and quality characteristics of starches isolated from potatoes using different processing methods from three commercial varieties: Lady Rosetta, Asterix and Challenger, for the first time in Pakistan. The analysis of variance revealed that starch yield significantly (P < 0.05) depended on total solids, peeling (12.7%, 12.0% and 12.0%) and unpeeling (15.0%, 14.0% and 14.0%) of potatoes compared to potato varieties for Lady Rosetta, Challenger and Asterix, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…Most starches are predominantly amylopectin (waxy corn starch can be up to 100% amylopectin) although some sources, such as high amylose corn starch, can have upward of 70% amylose (Lu et al, 2019). In general, it has been observed that higher percentages of amylose lead to more rigid films as denoted by a higher TS and EM and a simultaneous decrease in EAB as a result of an increased crystallinity (Cano, Jimenez, Chafer, Gonzalez, Dilute alkaline steeping (Gani et al, 2017;Van Hung et al, 2016;Ziegler et al, 2017) Potato 390 Mt Wet milling (Bergthaller, 2004;Bertoft & Blennow, 2016;Nawaz et al, 2020;Singh et al, 2018) Cassava root (Gous & Fox, 2017;Rittenauer, Kolesnik, Gastl, & Becker, 2016;You & Izydorczyk, 2002;Yu et al, 2017) Oat (Chu, 2014;Xu et al, 2017) Sago >90 kt Milling followed by wet sieving (Arshad, Zaman, Rawi, & Sarbini, 2018;Ehara, Toyoda, & Johnson, 2018;Karim, Tie, Manan, & Zaidul, 2008;Naseri et al, 2019) Note: Estimated yearly production in Indonesia, the largest producer of sago.…”
Section: The Complexities Of Starch and Starch Film Processingmentioning
confidence: 99%
“…Most starches are predominantly amylopectin (waxy corn starch can be up to 100% amylopectin) although some sources, such as high amylose corn starch, can have upward of 70% amylose (Lu et al, 2019). In general, it has been observed that higher percentages of amylose lead to more rigid films as denoted by a higher TS and EM and a simultaneous decrease in EAB as a result of an increased crystallinity (Cano, Jimenez, Chafer, Gonzalez, Dilute alkaline steeping (Gani et al, 2017;Van Hung et al, 2016;Ziegler et al, 2017) Potato 390 Mt Wet milling (Bergthaller, 2004;Bertoft & Blennow, 2016;Nawaz et al, 2020;Singh et al, 2018) Cassava root (Gous & Fox, 2017;Rittenauer, Kolesnik, Gastl, & Becker, 2016;You & Izydorczyk, 2002;Yu et al, 2017) Oat (Chu, 2014;Xu et al, 2017) Sago >90 kt Milling followed by wet sieving (Arshad, Zaman, Rawi, & Sarbini, 2018;Ehara, Toyoda, & Johnson, 2018;Karim, Tie, Manan, & Zaidul, 2008;Naseri et al, 2019) Note: Estimated yearly production in Indonesia, the largest producer of sago.…”
Section: The Complexities Of Starch and Starch Film Processingmentioning
confidence: 99%
“…Nawaz et al. (2020) also found that LR had maximum total solids. Total solids and specific gravity of potatoes depend on the growing conditions, phenotype, and storage conditions (Marwaha et al., 2005).…”
Section: Resultsmentioning
confidence: 89%
“…The results showed that Caruso variety had significantly (p < .05) maximum value of total solids followed by LR as compared to other varieties, while Sterna had low content of total solids. Nawaz et al (2020) also found that LR had maximum total solids. Total solids and specific gravity of…”
Section: Total Solids and Specific Gravitymentioning
confidence: 84%
See 2 more Smart Citations